The effect of powerful ultrasonic assistance during pressing on structural and luminescent properties of YAG : Ce; Optics and Spectroscopy; № 5 - Vol. 131 - Valiev D. T. Damir Talgatovich; Khasanov O. L. Oleg Leonidovich; Dvilis E. S. Edgar Sergeevich; Paygin V. D. Vladimir Denisovich; Lin Chaolu; Stepanov S. A. Sergey Aleksandrovich (2023, 2023)
Yttrium aluminum garnet (YAG) ceramics doped with Ce3+ was prepared by dry compaction using the common uniaxial pressing under powerful ultrasound assistance (PUA). The structure and luminescent properties of sintered ceramics were investigated. It was demonstrated that the powerful ultrasonic assistant during the dry pressing has a positive effect on the structural and luminescent characteristics of YAG : Ce3+ ceramics. The sintered material consolidation is very intensive accompanied by a decrease in the number of pores and grain growth at a sintering temperature of 1650 ◦C. The luminous efficiency of YAG : Ce3+ ceramics vary from 120 to 219 lm/W (without ultrasound treatment) and from 120 to 250 lm/W (prepared with ultrasound conditions) closely related with the phase purity and implicitly with sintering temperature. It was demonstrated the positive effect of PUA on the thermal properties of ceramics